Insights into the binding of paclitaxel to human serum albumin: multispectroscopic studies. (15th May 2013) - Yang, Xiuli; Ye, Zuowu; Yuan, Yong; Zheng, Zaoqian; Shi, Jiana; Ying, Yin; Huang, Ping
ABSTRACT: The interaction of paclitaxel with human serum albumin (HSA) was studied using fluorescence, resonance light scattering, ultraviolet‐visible, circular dichroism and Fourier transform infrared spectroscopy at pH 7.4. Fluorescence data revealed that the fluorescence quenching of HSA by paclitaxel was a static quenching procedure. Time‐resolved fluorescence data also confirmed the quenching mode, which present a constant decay time of about 5 ns. The binding sites were approximately 1 and the binding constant suggested a weak association (324/M at 298 K), which is helpful for the release of the drug to targeted organs. The thermodynamic parameters, Δ G ○, Δ H ° and Δ S ° were calculated as – 1.06 × 10 4  J/mol, 361 J/mol per K and 9.7 × 10 4  J/mol respectively at 298 K, suggesting that binding was spontaneous and was driven mainly by hydrophobic interactions. The binding distance between HSA and paclitaxel was determined to be 2.23 nm based on the Förster theory. Analysis of circular dichroism, ultraviolet‐visible, three‐dimensional fluorescence, Fourier transform infrared and resonance light scattering spectra demonstrated that HSA conformation was slightly altered in the presence of paclitaxel and dimension of the individual HSA molecules were larger after interacting with paclitaxel. These results were confirmed by a molecular docking study. Copyright © 2013 John Wiley & Sons, Ltd.